An updated safety review of the drug treatments for idiopathic pulmonary fibrosis. Issue 9 (2nd September 2021) - Sgalla, Giacomo; Comes, Alessia; Richeldi, Luca
ABSTRACT: Introduction: The approval of antifibrotic agents nintedanib and pirfenidone revolutionized the management of idiopathic pulmonary fibrosis (IPF). These treatments showed acceptable tolerability in randomized-clinical trials; however, they have been associated with a spectrum of potential side effects which require careful assessment of risks and benefits in the individual patient before commencing and during antifibrotic therapy. Areas covered: The accrued evidence on safety of nintedanib and pirfenidone is summarized, from the first randomized clinical trials to the open-label extension studies and post-marketing clinical experiences which helped clarify the long-term tolerability of these drugs. Expert opinion: The data collected over the last years confirmed the comparable tolerability profile of nintedanib and pirfenidone. The physician's assessment of expected side effects may help decide the optimal first-line therapy for the individual patient. Patient's counseling during treatment remains essential to manage emerging adverse events and eventually inform the decision of drug discontinuation.